Health monitoring in petrochemical vessels - Azizi, Aydin; Ashkzari, Ali (Trans Tech Publications Ltd ttp@transtec.ch, 2014)
Industrial structures deteriorate generally in an uncontrollable rate. To assess the shortterm impact due to hazards and the long-term deterioration process due to physical aging and routine operation, structural health monitoring (SHM) is proposed. In this paper as a model of vessel a simply supported beam under constant distributed force is investigated. The objective is to estimate the severity of damage in a known location with sensing devices. As no actuation is consider the problem is solved statically. Finite element method by using MATLAB software to calculate the global stiffness matrix of the smart beam has been applied. It is expected the results show that higher severity of damage causes higher deflection and higher sensor of voltage. © (2014) Trans Tech Publications, Switzerland.
2nd International Conference on Materials, Transportation and Environmental Engineering, CMTEE 2014 -- 2014-07-30 through 2014-07-31 -- Kunming -- 114820
Keywords: Damage detection; Smart beam; Structural health monitoring